LEKSIKO SEMANTIS KATA SIFAT DALAM KUMPULAN CERPEN LALAKI’NA TUNGTUNG PEUTING KARANGAN TIKTIK RUSYANI - M.S. Rahayu; Fahmi Rakhman (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2018)
Regional of Sunda published in many literary works that are not coupled with an understanding of the vocabulary of the language. One of kind words in which there are said plumb. Though the vocabulary to give effect to the understanding when communicating. Said plumb have appeared in the literature. Words can plumb give snapshot of the state, comparing a case, reinforce and said goods. Research conducted has the purpose of which describe the entire soy plumb in the book collection shoert story of Lalaki na Tungtung Peuting, know the type, shape, and the lexical meaning plumb sauce in a book of that short story. The method used is descriptive analysis methods. Data collection techniques were used that technique literature. Based on research, there are 1403 frequency of appearance of the word plumb. Divided by type and shape. On this kind of plumb said there are 340 words that appear as much as 988, divided into seven types carpenter said. That kind of word carpenter by color five words with a frequency of 15 times. Type the word plumb based form of 19 words with a frequency of 50 times. Type the word plumb based character 71 words with a frequency of 231 times. Type the word plumb based on the perception of 99 words with a frequency of 215 times. Type the word plumb by a sense of 84 words with a frequency of 261 times. Type the word plumb by size 58 words with a frequency of 193 times. Type the word plumb klasifikatoris five words with frequency appears 15 times. There are four forms of the word plumb. Forms of the word plumb salancar there are 340 words with a frequency of 988 times. Forms rundayan 189 words with a frequency of 297 times. Forms rajekan 50 words with a frequency of 73 times. Forms kantetan 38 words with a frequency of 45 times. There are also 340 lexical meaning of the word plumb. Use of this study are expected results of this study could address the issue of the emergence of literature that is not coupled with an understanding of the vocabulary of the language